Recurrent Femoral Artery Pseudoaneurysm: anticoagulant no more a life savior - Firdaus Mohd Hayati; Nornazirah Azizan; Aishath Azna Ali; Azim Idris (2016)
Femoral artery pseudoaneurysm is a devastating complication after arterial access. It may thrombose spontaneously with conservative management. Failure to thrombose is multifactorial. We present a case of iatrogenic femoral artery pseudoaneurysm, developed recurrence after consumption of anticoagulant, which was surgically treated using traditional open repair